2016
DOI: 10.1037/dev0000147
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and objective peer approval evaluations and self-esteem development: A test of reciprocal, prospective, and long-term effects.

Abstract: A large body of literature suggests a clear, concurrent association between peer approval and self-esteem in adolescence. However, little empirical work exists on either the prospective or reciprocal relation between peer approval and self-esteem during this age period. Moreover, it is unclear from past research whether both subjectively perceived peer approval and objectively measured peer approval are related to subsequent self-esteem over time (and vice versa) and whether these paths have long-term associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 72 publications
(107 reference statements)
3
45
0
Order By: Relevance
“…Self‐direction and power, but also achievement values, were more likely to grow in importance with time than to decline. Developing an independent identity during adolescence may take the form of self‐promotion, as adolescents seek to augment their social status (Gruenenfelder‐Steiger et al, ). This tendency may be strengthened by the educational contexts in which they spend much of their time (e.g., the school setting).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Self‐direction and power, but also achievement values, were more likely to grow in importance with time than to decline. Developing an independent identity during adolescence may take the form of self‐promotion, as adolescents seek to augment their social status (Gruenenfelder‐Steiger et al, ). This tendency may be strengthened by the educational contexts in which they spend much of their time (e.g., the school setting).…”
Section: Discussionmentioning
confidence: 99%
“…This process may lead to a unique, idiosyncratic personal identity (e.g., Meeus, ). At the same time, to support the process of becoming competent, autonomous individuals, adolescents want to be acknowledged by society (e.g., Van der Giessen, Branje, & Meeus, ) and look for acceptance from their peers (Gruenenfelder‐Steiger, Harris, & Fend, ). In some cases, however, the need for recognition and popularity can lead to acts of control or aggression (Cillessen & Rose, ).…”
Section: Introductionmentioning
confidence: 99%
“…Our findings should be replicated with more diverse samples (e.g., Bohanek et al., ; Reese & Fivush, for research with fathers). In addition, future research could examine reminiscing conversations with individuals other than parents (e.g., peers; see Gruenenfelder‐Steiger, Harris, & Fend, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefor it is surprising that we still know little about the role of feedback to self-disclosure in online communication and its effects on people's self-esteem. The few studies that have investigated the effects of online feedback have shown that receiving confirming feedback augments effects of selective self-presentation on how people perceive themselves (Gruenenfelder-Steiger, Harris, & Fend, 2016;Harter, 2012a;Srivastava & Beer, 2005). Yet, there is also reason to believe that the effects of online versus face-to-face feedback might be different.…”
Section: Introductionmentioning
confidence: 92%